2018 Vegetable Production Handbook Chapter 18: Tomato Production - Josh H. Freeman; Eugene J. McAvoy; Nathan S. Boyd; Ramdas Kanissery; Monica Ozores-Hampton; Hugh A. Smith; Johan Desaeger; Joseph W. Noling; Gary E. Vallad (EDIS)
This 45-page fact sheet is chapter 18 of the 2018 Vegetable Production Handbook. Written by Josh H. Freeman, Eugene J. McAvoy, Nathan S. Boyd, Ramdas Kanissery, Monica Ozores-Hampton, Hugh A. Smith, Johan Desaeger, Joseph W. Noling, and Gary E. Vallad, and published by the Horticultural Sciences Department, 2018.